CE-SIR GRANT - Medikids: Empowering young minds for quality use of medicine / Nor Elyzatul Akma Hamdan and Dr. Gurmeet Kaur Surindar Singh - Hamdan, Nor Elyzatul Akma; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
MediKids for primary school children was held on June 17th, 2023, at the Faculty of Pharmacy, Universiti Teknologi MARA (UiTM), Puncak Alam. Eighty school children from Sekolah Kebangsaan Puncak Alam 2 were involved in this program. MediKids aims to instill in the younger generation the knowledge to make informed decisions about their health. The "Pharmatopia" programme, under the banner of MediKids, was designed with the objective of simplifying complex medical information and presenting it in an engaging and age-appropriate manner.